Alteration of affective Theory of Mind in amnestic mild cognitive impairment. Issue 1 (5th November 2012) - Poletti, Michele; Bonuccelli, Ubaldo
<x xml:space="preserve">Abstract</x> The concept of amnestic mild cognitive impairment (aMCI) concerns a population of older individuals at high risk of developing probable Alzheimer's disease (AD). Impairments of the cognitive component of Theory of Mind (ToM), that is the inference about other people's beliefs, have been well documented in AD; on the contrary, controversial findings have been reported on the affective component of ToM (inference about other's feelings), a process mainly based on medial portions of the prefrontal cortex. The current study aimed at evaluating the affective component of ToM in aMCI subjects. Twenty aMCI subjects and 20 age‐matched healthy controls (HC) underwent a standard neuropsychological assessment and the assessment of affective ToM with the full 36‐item version of reading the mind in the eyes (RME). Although aMCI subjects had formal impaired performances only in memory tasks, HC outperformed aMCI subjects in several cognitive tasks, including also the RME (mean RME scores 21.7 ± 3.0 vs. 17.0 ± 3.8%; 60.3% of correct answers vs. 47.2%). The lower RME performance of aMCI patients provides the first empirical evidence that aMCI may be associated with difficulties in tasks of affective ToM, in accordance with recent findings of early difficulties of aMCI patients in other processes that are mainly dependent on the medial prefrontal cortex, such as reversal learning and decision making under ambiguity. Findings of the current study need further empirical confirmation in larger samples of aMCI patients and also the investigation of other MCI subtypes is needed.